Lail Adventure: Perancangan Script Game Edukasi Islami Anak Menggunakan Metode Narrative Desain - Zidan Tri Anggoro Zidan (Jurnal Repositor, 2026)
Education serves as a crucial foundation for the profress of a nation, and effective education necessitates an efficient system, including spiritual education. Muhammadiyah, as a leading advocate in Kemuhammadiyahan learning, faces various challenges, particularly in terms of teaching strategies in the era of globalization. One proposed solution is the use of interactive learning media, suc as educational games. In this context, this study aims to explore the implementation os script and story in the educational game “Lail Adventure” themed around Kemuhammadiyahan. The research methodology employed is Narrative Desain, suitable for game development as it provides interactive experiences through storytelling in the game. Through needs analysis, concept development, narrative analysis, and level design, this research yields a comprehensive understanding of educational game creation. The research findings indicate that the game “Lail Adventure” targets children aged 6 – 12 years old and provides significant benefits in learning. In concept development, the game adopts the action genre and is set in a nighttime world where the main character aims to revive the night by going to the mosque. Narraive analysis reveals that a linear narrative approach is chosen to provide structured gameplay experiences. Level desain focuses on increasing difficulty as players progress through different arenas. The design of islamoc educational game script using narrative design illustrates detaild steps, from needs analysis to level desain. This, this research offers a significant contribution to the development of educational game that integrate Islamic values with modern technology, enriching children’s learning experiences in a engaging and effective manner.